Outdoor anti-aging PVC fence special modified material and preparation method thereof
Patent Information
- Application Number
- CN202611272214.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-27
AI Technical Summary
针对现有技术的不足,本发明提供了一种户外抗老化PVC护栏专用改性材料及其制备方法,解决了现有户外PVC护栏材料及型材在复杂外露截面中存在局部耐候保护能力与实际老化负荷不匹配的问题,特别是在棱边、倒角、卡扣槽外唇及筋条根部等位置,容易因局部保护层薄化、老化影响层加深及应力集中而优先发生粉化、黄变和老化脆裂
通过使耐候表层覆盖外露平面、棱边、倒角、卡扣槽外唇及筋条根部,并使外露薄弱区域的耐候表层厚度与表层老化影响深度相匹配,可使户外服役中最易受紫外、湿热和装配应力共同作用的局部区域保持连续耐候保护,降低芯层提前暴露、局部粉化、黄变及裂纹扩展风险。
Smart Images

Figure CN122978613A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of PVC modified materials technology, specifically to a modified material for outdoor anti-aging PVC guardrails and its preparation method. Background Technology
[0002] PVC fences are widely used in outdoor applications such as residential courtyards, municipal roads, coastal walkways, park fencing, farm and ranch boundaries, and scenic area railings due to their lightweight, corrosion resistance, ease of extrusion molding, and low maintenance costs. These fences typically consist of hollow horizontal bars, posts, railing panels, or snap-fit connectors, and their cross-sections often include exposed surfaces, chamfers, edges, snap-fit grooves, interlocking lips, and internal ribs. Current PVC fence materials mostly utilize PVC resin combined with heat stabilizers, titanium dioxide, impact modifiers, fillers, lubricants, and light stabilizers to create a weather-resistant formula. Some profiles also employ a layered extrusion process to balance appearance, weather resistance, and material cost.
[0003] The above-mentioned routes can meet general outdoor use requirements, but in environments with high UV radiation, high humidity and heat, salt spray, wind and sand, spray scale, acidic deposits, and repeated day-night temperature differences, local failures of complex cross-section profiles are still quite prominent. In particular, areas such as edges, outer lips of snap-fit grooves, chamfers, and the roots of ribs are more prone to forming local weak areas when the melt changes direction, stretches, and converges within the die head; at the same time, these areas have greater curvature, concentrated assembly stress, and uneven cooling and shrinkage, and are more likely to retain water films, salt dust, and contaminant particles during service, causing processes such as UV oxidation, thermo-oxidative aging, additive migration, PVC dechlorination, and filler interface debonding to occur simultaneously.
[0004] For white or light-colored railings, the distribution of titanium dioxide in certain areas, the surface coating condition, and the presence of light stabilizers can affect surface chalking and color difference changes. For dark-colored or wood-grain railings, surface heat absorption and temperature rise will further amplify thermo-oxidative aging and residual stress release. Evaluating products solely based on average color difference, average surface thickness, or initial impact strength in planar areas is insufficient to reflect the risks of chalking, yellowing, whitening, microcrack propagation, and snap-fit cracking in these vulnerable areas after prolonged exposure to sunlight and humid heat cycles. Once localized chalking develops, it increases surface roughness and promotes continued adhesion of contaminants; localized embrittlement reduces the impact resistance and warping stability of joints, ultimately affecting the railing's appearance consistency, assembly reliability, and long-term service life. Summary of the Invention
[0005] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a modified material specifically for outdoor anti-aging PVC guardrails and its preparation method. It solves the problem that existing outdoor PVC guardrail materials and profiles have a mismatch between local weather protection capabilities and actual aging loads in complex exposed sections. In particular, at edges, chamfers, outer lips of snap-fit grooves, and the roots of reinforcing bars, powdering, yellowing, and aging cracking are prone to occur due to thinning of the local protective layer, deepening of the aging influence layer, and stress concentration.
[0006] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: This invention provides a modified material specifically for outdoor anti-aging PVC guardrails, comprising a co-extruded weather-resistant surface layer and a structural core layer. The weather-resistant surface layer at least covers the exposed planes, exposed edges, chamfers, outer lips of the snap-fit grooves, and the outer area near the root of the reinforcing ribs of the PVC guardrail profile. The weather-resistant surface layer accounts for 5.0%-24.0% of the total mass of the profile. The average thickness of the weather-resistant surface layer on the exposed plane is 0.15-0.80 mm, and the thinnest thickness of the weather-resistant surface layer on the exposed edges, chamfers, snap-fit grooves, root of the reinforcing ribs, or exposed corners is 0.12-0.60 mm. The ratio of the thinnest thickness of the weather-resistant surface layer to the surface aging influence depth determined by the layer-by-layer carbonyl index method is 1.2-4.0.
[0007] Based on 100 parts of PVC resin in the weather-resistant surface layer, the weather-resistant surface layer comprises 4.5-12.0 parts of rutile titanium dioxide coated on the surface, 0.05-0.80 parts of nano-cerium oxide, 0.6-4.0 parts of layered double hydroxide or hydrotalcite, a lead-free calcium-zinc composite stabilizing system, a light stabilizing system composed of high molecular weight hindered amine light stabilizers and benzotriazole or triazine UV absorbers, an impact modification system, fillers, and a lubrication system. The lead-free calcium-zinc composite stabilizing system includes calcium-zinc composite stabilizers, β-diketone auxiliary stabilizers, phosphite antioxidants, and hindered phenolic antioxidants; the light stabilizing system includes high molecular weight hindered amine light stabilizers and benzotriazole or triazine UV absorbers.
[0008] This invention also provides a method for preparing the modified material for outdoor anti-aging PVC guardrails, including raw material pretreatment, segmented hot mixing of surface material, preparation of core material, cold mixing and curing, rheological calibration before extrusion, co-extrusion plasticizing, die head thickness maintenance, vacuum shaping, stepped cooling and cutting; wherein, the surface dry mix is subjected to three stages of hot mixing in sequence. In the first stage, PVC resin is mixed with calcium-zinc composite stabilizer, hydrotalcite, β-diketone auxiliary stabilizer, phosphite antioxidant, hindered phenol antioxidant and part of internal lubricant. In the second stage, rutile titanium dioxide with surface coating, nano-cerium oxide pre-dispersed with surface-modified calcium carbonate and filler are added. In the third stage, high molecular weight hindered amine light stabilizer, benzotriazole or triazine ultraviolet absorber, CPE, core-shell ACR impact modifier, processing aid ACR and remaining lubricant are added.
[0009] (III) Beneficial Effects This invention provides a modified material specifically for outdoor anti-aging PVC guardrails and its preparation method, which has the following beneficial effects: By covering exposed surfaces, edges, chamfers, snap groove outer lips, and rib roots with a weather-resistant surface layer, and matching the thickness of the weather-resistant surface layer in exposed weak areas with the depth of surface aging effects, continuous weather protection can be maintained in the local areas most susceptible to the combined effects of ultraviolet rays, damp heat, and assembly stress during outdoor service, reducing the risk of premature core layer exposure, localized powdering, yellowing, and crack propagation.
[0010] The surface is coated with rutile titanium dioxide, nano-cerium oxide, layered double hydroxide or hydrotalcite, lead-free calcium-zinc composite stabilizing system, hindered amine light stabilizer and ultraviolet absorber to form a synergistic shielding and stabilizing system in the weather-resistant surface layer. This system can simultaneously weaken the photocatalytic side effects of titanium dioxide, buffer the acidic microenvironment formed by the dehydrochlorination of polyvinyl chloride, and maintain the effective retention of light stabilizer.
[0011] The combination of chlorinated polyethylene, core-shell acrylate impact modifiers, processing aids, and surface-modified fillers helps to balance toughness, rigidity, and dimensional stability, ensuring that the snap-fit grooves, edges, and rib roots retain good impact and crack resistance even after aging. The combined use of segmented hot mixing, pre-extrusion rheological calibration, co-extrusion compensated runners, vacuum setting, and stepped cooling reduces powder agglomeration, additive migration, surface thinning, and residual cooling stress, resulting in more stable molding quality and long-term outdoor reliability for complex cross-section guardrail profiles. Attached Figure Description
[0012] Figure 1 This is a schematic cross-sectional view of the layered structure of the PVC guardrail profile of the present invention; Figure 2 This is a partially enlarged schematic diagram of the thinnest weather-resistant surface layer at the exposed edges and snap-fit grooves of the present invention; Figure 3 This is a schematic diagram showing the enrichment and distribution of weather-resistant agents in the weather-resistant surface layer and structural core layer of the present invention; Figure 4 This is a flowchart illustrating the preparation process of the modified outdoor anti-aging PVC guardrail material of the present invention. Figure 5 This is a schematic diagram of the three-stage hot mixing feeding sequence of the surface dry mix of the present invention; Figure 6 This is a schematic diagram of the co-extrusion die head compensation flow channel and online thickness measurement feedback control of the present invention. Detailed Implementation
[0013] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0014] The present invention will be further described below with reference to embodiments. Unless otherwise stated, all parts are parts by weight, and the surface layer material or core layer material is calculated based on 100 parts of PVC resin in the corresponding layer. The following embodiments are used to illustrate possible implementations of the present invention and should not be construed as limiting the scope of protection.
[0015] Please see Figures 1-6 This invention provides a modified material for outdoor anti-aging PVC guardrails and its preparation method.
[0016] I. Modified Materials and Profile Structures The modified material for outdoor anti-aging PVC guardrails of the present invention is used to form PVC guardrail profiles with a structural core layer and a weather-resistant surface layer. The weather-resistant surface layer at least covers the exposed planes, exposed edges, chamfers, outer lips of the snap-fit grooves, and the outer region near the root of the reinforcing ribs of the guardrail profile. The structural core layer forms the main wall of the hollow crossbar and the internal reinforcing ribs. The weather-resistant surface layer accounts for 5.0%-24.0% of the total mass of the profile, preferably 8.0%-18.0%; the average thickness of the weather-resistant surface layer on the exposed plane is 0.15-0.80 mm, preferably 0.22-0.50 mm; the thinnest thickness of the weather-resistant surface layer at the edges, chamfers, snap-fit grooves, root of the reinforcing ribs, or exposed corners is 0.12-0.60 mm, preferably 0.18-0.38 mm.
[0017] In a preferred embodiment, the ratio of the thinnest weather-resistant surface layer thickness in the exposed area to the surface aging influence depth determined by the layer-by-layer carbonyl index method is 1.2-4.0, preferably 1.6-2.8. The surface aging influence depth refers to the depth at which the material sample, after being subjected to accelerated aging under fluorescent ultraviolet light, is removed layer by layer from the outer surface inward and aging characteristic indicators are measured until the indicators recover to the reference range of the unaged core layer.
[0018] II. Composition of Weather-Resistant Surface Material The weather-resistant surface material includes PVC resin, rutile titanium dioxide coated on the surface, nano-cerium oxide, layered double hydroxide or hydrotalcite, lead-free calcium-zinc composite stabilizing system, light stabilizing system composed of high molecular weight hindered amine light stabilizer and benzotriazole or triazine UV absorber, impact modification system, filler and lubrication system.
[0019] The amount of rutile titanium dioxide coated on the surface is 4.5-12.0 parts, preferably 6.0-9.5 parts; its particle size D50 is 0.18-0.42 μm, preferably 0.22-0.32 μm; the surface has one or more inorganic coating layers selected from silica, alumina, and zirconium oxide, and the coating amount is 1.5%-8.0% of the titanium dioxide mass, preferably 3.0%-6.5%. The amount of nano-cerium oxide is 0.05-0.80 parts, preferably 0.12-0.45 parts; its particle size D50 is 20-120 nm, preferably 35-80 nm. The amount of layered double hydroxide or hydrotalcite is 0.6-4.0 parts, preferably 1.2-2.8 parts; the Mg / Al molar ratio is 1.8-4.0, preferably 2.0-3.2.
[0020] The lead-free calcium-zinc composite stabilizing system comprises a calcium-zinc composite stabilizer, a β-diketone auxiliary stabilizer, a phosphite antioxidant, and a hindered phenol antioxidant. The amount of the calcium-zinc composite stabilizer is 2.5-6.5 parts, preferably 3.2-4.8 parts; the Ca / Zn molar ratio is 2.0-7.0, preferably 3.0-5.5. The amount of the β-diketone auxiliary stabilizer is 0.05-0.60 parts, preferably 0.10-0.35 parts; the amount of the phosphite antioxidant is 0.05-0.50 parts, preferably 0.08-0.25 parts; and the amount of the hindered phenol antioxidant is 0.03-0.35 parts, preferably 0.06-0.18 parts.
[0021] The light-stabilizing system comprises a high molecular weight hindered amine light stabilizer and a benzotriazole or triazine UV absorber. The high molecular weight hindered amine light stabilizer has a number average molecular weight of 900-6000 g / mol, preferably 1500-4500 g / mol, and is used in an amount of 0.20-1.20 parts, preferably 0.35-0.80 parts; the UV absorber is used in an amount of 0.20-1.20 parts, preferably 0.35-0.85 parts; the mass ratio of the high molecular weight hindered amine light stabilizer to the UV absorber is 0.5:1-2.5:1, preferably 0.7:1-1.6:1.
[0022] The impact modification system includes CPE, core-shell ACR impact modifier, and processing aid ACR. The amount of CPE is 2.0-9.0 parts, preferably 3.5-6.5 parts, and the chlorine content is 32%-40%, preferably 34%-37%; the amount of core-shell ACR impact modifier is 2.0-8.0 parts, preferably 3.0-5.5 parts, and the particle size D50 is 100-420 nm, preferably 150-300 nm; the amount of processing aid ACR is 0.6-2.2 parts, preferably 0.8-1.5 parts.
[0023] The filler comprises surface-modified calcium carbonate and flake mica powder or talc powder, wherein the amount of surface-modified calcium carbonate is 4-25 parts, preferably 8-16 parts, and the D50 is 0.6-3.5 μm, preferably 1.0-2.2 μm; the amount of flake mica powder or talc powder is 2-14 parts, preferably 4-9 parts, and the aspect ratio is 8-50, preferably 12-35. The amount of lubrication system is 0.4-1.5 parts, preferably 0.7-1.1 parts.
[0024] III. Composition of Structural Core Material The structural core material includes PVC resin, titanium dioxide, a lead-free calcium-zinc composite stabilizing system, an impact-modifying system, fillers, and a lubrication system. Based on 100 parts of PVC resin in the core layer, the amount of rutile titanium dioxide in the core layer is 0.3-4.0 parts, preferably 0.8-2.5 parts; the amount of nano-cerium oxide is 0-0.15 parts, preferably 0-0.08 parts; the amount of calcium-zinc composite stabilizer is 2.5-5.5 parts, preferably 3.0-4.2 parts; the amount of hydrotalcite or layered double hydroxide is 0.3-2.5 parts, preferably 0.6-1.8 parts; the amount of β-diketone auxiliary stabilizer is 0.05-0.35 parts, preferably 0.08-0.20 parts; the amount of phosphite antioxidant is 0.03-0.30 parts, preferably 0.06-0.18 parts; and the amount of hindered phenolic antioxidant is 0.02-0.20 parts, preferably 0.03-0.10 parts.
[0025] In the structural core layer, the amount of CPE is 3.0-8.0 parts, preferably 4.5-6.5 parts; the amount of core-shell ACR impact modifier is 1.0-5.0 parts, preferably 2.0-3.5 parts; the amount of processing aid ACR is 0.5-1.8 parts, preferably 0.7-1.2 parts; the amount of surface-modified calcium carbonate is 8-25 parts, preferably 12-20 parts; the amount of flake mica powder or talc powder is 2-14 parts, preferably 4-9 parts; and the amount of lubrication system is 0.5-1.5 parts, preferably 0.8-1.2 parts.
[0026] In a preferred embodiment, the titanium element signal intensity in the weather-resistant surface layer is higher than that in the structural core layer, the cerium element signal in the surface layer is significantly higher than that in the structural core layer, the Mg / Al signal in the surface layer is higher than that in the structural core layer, and the characteristic peak intensity of the light stabilizer in the surface layer is higher than that in the structural core layer, thereby forming an enriched distribution of weather-resistant agent.
[0027] IV. Preparation Method The preparation method includes raw material pretreatment, segmented hot mixing of surface material, segmented hot mixing of core material, cold mixing and curing, rheological calibration before extrusion, co-extrusion plasticizing, die head thickness maintenance, vacuum shaping, stepped cooling, and cutting. Before production, PVC resin, titanium dioxide, surface-modified calcium carbonate, flake mica powder, hydrotalcite, and nano-cerium oxide are placed in a sealed transfer silo for equilibration for 4-12 hours, preferably 6-10 hours; the workshop temperature is controlled at 20-30℃, preferably 22-26℃; and the relative humidity is controlled at 35%-60%, preferably 40%-50%.
[0028] The hot mixing process employs a vertical high-speed hot mixer with three layers of angled blades. The total volume of the hot mixer is 300-800L, and the effective working volume is 200-560L. The filling rate is controlled at 60%-80%, preferably 68%-76%. The unit loading power during the hot mixing stage is controlled at 0.18-0.32kW / kg. The hot mixing temperature is primarily controlled by an armored thermocouple inserted into the center of the powder bed, with the infrared temperature of the pot wall used as an auxiliary monitoring value.
[0029] During the first stage of hot mixing of the surface layer material, the surface layer PVC resin is first added to a high-speed hot mixer and stirred at low speed for 60-120 seconds, preferably 80-100 seconds. Subsequently, calcium-zinc composite stabilizer, hydrotalcite, β-diketone auxiliary stabilizer, phosphite antioxidant, hindered phenol antioxidant, and part of the internal lubricant are added sequentially. The impeller speed is adjusted to 720-780 rpm, and the material is heated to 70-80℃, preferably 73-77℃, at a heating rate of 3.5-5.0℃ / min.
[0030] During the second stage of hot mixing of the surface material, the rutile-coated titanium dioxide is continuously added via a screw feeder at a rate of 0.8-1.8 kg / min, preferably 1.1-1.5 kg / min. The nano-cerium oxide is not directly fed into the high-speed hot mixer; instead, it is first pre-dispersed with surface-modified calcium carbonate at a mass ratio of 1:8-1:12 in a closed premixer for 120-300 seconds, preferably 150-210 seconds, to form a carrier dilution powder before being added to the main pot. Subsequently, the remaining surface-modified calcium carbonate and flake mica powder are added, and the temperature is raised to 90-100℃, preferably 93-97℃, at a heating rate of 2.0-4.0℃ / min.
[0031] During the third stage of hot mixing of the surface material, after the temperature inside the pot reaches 90-100℃, high molecular weight hindered amine light stabilizer, ultraviolet absorber, CPE, core-shell ACR impact modifier and processing aid ACR are added in sequence, and the blade speed is controlled at 690-730 rpm; then the remaining lubricant is added, and the temperature is raised to 113-116.5℃, preferably 114-116℃, at a heating rate of 2.0-3.0℃ / min.
[0032] In addition to reaching a temperature of 113-116.5℃ at the end of the surface layer hot mixing process, the following conditions should also be met: the main motor current fluctuation should not exceed ±4.5% within 60 seconds; no wax spots should appear after the sampled powder is lightly pressed with a glass slide; and the agglomerate on the 2.0mm sieve should be less than 0.15% by mass when sieved 30 minutes after discharge. Immediately after hot mixing, the material should be discharged into a cold mixer. Discharge should occur when the material temperature drops to 40-50℃, preferably 43-47℃, and the material should be matured at 20-35℃ for 4-24 hours, preferably 8-16 hours, to obtain the surface layer dry mix.
[0033] Before extrusion, the surface dry mix and the core dry mix are taken separately and tested by a torque rheometer, capillary rheometer or dynamic mechanical rheometer. Under the conditions of 185°C and shear rate of 100 s^-1, the ratio of the apparent viscosity of the surface melt to the apparent viscosity of the core melt is controlled to be 0.70-1.45, preferably 0.85-1.20, and more preferably 1.02-1.08.
[0034] Co-extrusion plasticizing employs a core layer conical twin-screw extruder and a surface layer co-extruder in parallel production. The measured temperature of the core layer melt is controlled at 170-185℃, preferably 176-181℃; the measured temperature of the surface layer melt is controlled at 176-190℃, preferably 181-186℃; the die inlet, middle section, and outlet temperatures are controlled at 180-190℃, 183-193℃, and 184-195℃, respectively. The co-extrusion die adopts a dual-channel structure with independent core layer main channel and surface layer distribution channel. The surface layer distribution channel is equipped with replaceable flow-limiting gaskets in the planar area, edge area, and snap-fit groove area, allowing the surface material to receive 8%-15% higher local feed compensation at the edges and grooves compared to the planar area.
[0035] When the preform enters the first vacuum forming stage, the negative pressure is controlled at -0.040 to -0.085 MPa, preferably -0.055 to -0.070 MPa; the cooling water temperatures of the first, second, third, and fourth stages are controlled at 30-40℃, 24-32℃, 18-24℃, and 12-18℃ respectively. An online laser or ultrasonic thickness measurement system collects the surface thickness at the plane, edges, and locking groove every 5 seconds. Example
[0036] This embodiment produces a double-cavity hollow PVC guardrail crossbar profile with an external cross-section of 76.2mm × 50.8mm, a main body wall thickness of 2.70mm, and snap-fit grooves on both sides. The exposed edge radius is 1.20mm. The finished profile includes a structural core layer and a weather-resistant surface layer covering the exposed surface, wherein the weather-resistant surface layer accounts for 12.50% of the total mass of the profile, and the structural core layer accounts for 87.50%. The thickness of the weather-resistant surface layer on the flat exposed surface is controlled at 0.320±0.020mm, and the thinnest thickness of the weather-resistant surface layer at the edges, chamfers, snap-fit grooves, and rib roots is controlled at 0.240±0.020mm.
[0037] The surface dry mix is based on 100,000 kg of surface PVC resin, and includes 100,000 kg of PVC resin with a K value of 66.0 and a volatile content of less than 0.25%, 7,800 kg of silicon-aluminum-zirconium composite-coated rutile titanium dioxide, 0,250 kg of surface-treated nano-cerium oxide, 1,800 kg of hydrotalcite, 3,800 kg of calcium-zinc composite stabilizer, 0,180 kg of β-diketone auxiliary stabilizer, 0,150 kg of phosphite antioxidant, 0,100 kg of hindered phenol antioxidant, 0,500 kg of high molecular weight hindered amine light stabilizer, 0,550 kg of triazine UV absorber, 4,800 kg of CPE, 4,000 kg of core-shell ACR impact modifier, 1,100 kg of processing aid ACR, 8,000 kg of surface-modified calcium carbonate, 4,000 kg of flake mica powder, and 0,900 kg of lubrication system.
[0038] Among them, the D50 of the silicon-aluminum-zirconium composite-coated rutile titanium dioxide is 0.270 μm, and the coating amount is 5.20%; the D50 of the surface-treated nano-cerium oxide is 55.0 nm; the Mg / Al molar ratio of the hydrotalcite is 2.50, and the D50 is 0.900 μm; the Ca / Zn molar ratio of the calcium-zinc composite stabilizer is 4.20; the number average molecular weight of the high molecular weight hindered amine light stabilizer is about 3000 g / mol; the chlorine content of CPE is 35.5%; the D50 of the core-shell ACR impact modifier is 220 nm; the D50 of the surface-modified calcium carbonate is 1.500 μm; the aspect ratio of the flake mica powder is 25.0; and the lubrication system consists of 0.260 kg of polyethylene wax, 0.220 kg of oxidized polyethylene wax, 0.260 kg of calcium stearate, and 0.160 kg of stearic acid.
[0039] The core layer dry mix is based on 100,000 kg of core layer PVC resin, and includes 100,000 kg of PVC resin with a K value of 67.0 and a volatile content of less than 0.25%, 1.600 kg of rutile titanium dioxide, 0.030 kg of surface-treated nano-cerium oxide, 3.200 kg of calcium-zinc composite stabilizer, 1.000 kg of hydrotalcite, 0.120 kg of β-diketone auxiliary stabilizer, 0.100 kg of phosphite antioxidant, and hindered phenol. The composition includes 0.050 kg of antioxidant, 5.500 kg of CPE, 2.500 kg of core-shell ACR impact modifier, 0.900 kg of processing aid ACR, 16.000 kg of surface-modified calcium carbonate, 6.000 kg of flake mica powder, and 1.000 kg of lubrication system. The lubrication system consists of 0.300 kg of polyethylene wax, 0.250 kg of oxidized polyethylene wax, 0.300 kg of calcium stearate, and 0.150 kg of stearic acid.
[0040] Before production, PVC resin, titanium dioxide, calcium carbonate, mica powder, hydrotalcite, and nano-cerium oxide are placed in sealed transfer silos for equilibration for 8.0 hours. The workshop temperature is controlled at 24.0℃ and the relative humidity at 45.0%. The moisture content of the powders is tested before feeding, with the volatile matter content of PVC resin not exceeding 0.25%, and the moisture content of calcium carbonate and hydrotalcite not exceeding 0.20%. A 500L vertical high-speed hot mixer with three-layer angled blades and a 1000L cold mixer are used. The effective working volume of the hot mixer is 350L.
[0041] When preparing the surface dry mix, first add 100,000 kg of surface PVC resin to a high-speed mixer, set the impeller speed to 360.0 rpm, and idle for 90.0 seconds to form a uniformly turbulent white powder bed of PVC powder. Then, add 3,800 kg of calcium-zinc composite stabilizer, 1,800 kg of hydrotalcite, 0.180 kg of β-diketone auxiliary stabilizer, 0.150 kg of phosphite antioxidant, 0.100 kg of hindered phenolic antioxidant, and 0.260 kg of calcium stearate in sequence. Adjust the impeller speed to 720.0 rpm, and heat the material from 38.0℃ to 75.0℃ at a heating rate of 4.2℃ / min, and continue mixing for 120.0 seconds.
[0042] Subsequently, while maintaining the impeller speed at 720.0 rpm, 7.800 kg of silicon-aluminum-zirconium composite-coated rutile titanium dioxide was continuously added via a screw feeder at a rate of 1.300 kg / min. 0.250 kg of nano-cerium oxide was pre-dispersed with 2.000 kg of surface-modified calcium carbonate in a small, closed premixer at 1200.0 rpm for 180.0 seconds, and then added to the main pot as a carrier dilution powder. Following this, the remaining 6.000 kg of surface-modified calcium carbonate and 4.000 kg of flake mica powder were added, and the temperature was raised to 95.0℃ at a rate of 3.0℃ / min.
[0043] Once the temperature inside the pot reaches 95.0℃, add 0.500 kg of high molecular weight hindered amine light stabilizer, 0.550 kg of triazine UV absorber, 4.800 kg of CPE, 4.000 kg of core-shell ACR impact modifier, and 1.100 kg of processing aid ACR in sequence, and maintain the blade speed at 720.0 rpm; then add 0.260 kg of polyethylene wax, 0.220 kg of oxidized polyethylene wax, and 0.160 kg of stearic acid, and raise the temperature to 115.0℃ at a heating rate of 2.5℃ / min.
[0044] After reaching 115.0℃, the material is immediately discharged into a cold mixer, cold-mixed to 45.0℃, and then discharged. It is then allowed to stand and mature at 25.0℃ for 12.0 hours to obtain the surface dry mix. The core dry mix is prepared by weighing each component according to the core layer formula, using the same equipment and segmented mixing method as the surface mix. The hot mixing endpoint temperature of the core layer is 112.0℃, the cold mixing endpoint temperature is 45.0℃, and it is allowed to stand and mature at 25.0℃ for 12.0 hours.
[0045] Before extrusion, surface dry blends and core dry blends were taken separately and tested using a torque rheometer or capillary rheometer. Under conditions of 185.0℃ and a shear rate of 100.0 s⁻¹, the ratio of the apparent viscosity of the surface melt to that of the core melt was 1.04 ± 0.04. Co-extrusion plasticizing was performed using a core layer conical twin-screw extruder and a surface layer co-extruder in series. The measured temperature of the core melt was controlled at 178.5℃, and the measured temperature of the surface melt was controlled at 184.0℃. The die inlet, middle section, and outlet temperatures were set at 184.0℃, 187.0℃, and 188.0℃, respectively.
[0046] The core material mass flow rate is controlled at 131.25 kg / h, the surface material mass flow rate at 18.75 kg / h, and the total output at 150.00 kg / h using a loss-in-weight feeding system. The core pressure is controlled at 11.8 MPa, the surface pressure at 12.4 MPa, and the surface pressure to core pressure ratio is 1.05. The co-extrusion die adopts a dual-channel structure with independent core main channel and surface distribution channel. The opening height of the flow-limiting gasket in the planar area is 0.210 mm, the opening height of the edge compensation branch is 0.235 mm, and the opening height of the snap-fit groove outer lip compensation branch is 0.245 mm.
[0047] When the preform enters the first vacuum forming stage, the negative pressure is set to -0.064 MPa, and the cooling water temperatures for the first, second, third, and fourth stages are set to 36.0℃, 28.0℃, 20.0℃, and 15.0℃, respectively. The traction speed is set to 1.75 m / min. An online laser or ultrasonic thickness measurement system collects the surface thickness at the plane, edges, and snap-fit grooves every 5.0 seconds. After 30 minutes of stable operation, the exposed surface thickness is controlled at 0.320 ± 0.020 mm, and the thinnest surface thickness at the edges, chamfers, snap-fit grooves, and rib roots is controlled at 0.240 ± 0.020 mm.
[0048] Samples were taken from the 10th, 30th, and 60th profiles after stable operation to prepare polished cross-section discs. The surface thickness of the planes, edges, chamfers, snap-fit grooves, and rib roots was measured using an optical microscope. SEM-EDS was used to perform a line scan along the outer surface towards the core layer to record the elemental distributions of Ti, Ce, Mg, Al, and Zn. ATR-FTIR was used to examine the characteristic peaks of the surface light stabilizer and the carbonyl index profile after aging through layer-by-layer polishing.
[0049] Experimental Example The following experimental examples illustrate the sample preparation, comparative sample setup, testing methods, and test results of the modified materials and their preparation methods of this invention. The data tables in the experimental examples are only used for the centralized presentation of experimental results and comparative data.
[0050] I. Sample Preparation PVC guardrail profile samples of Example 1 and Comparative Examples 1-5 were prepared according to the variables listed in Table 1. Example 1 adopted a co-extrusion structure of weather-resistant surface layer and structural core layer; each comparative example was set to address the following issues: homogeneous baseline of single layer, absence of inorganic synergistic components, absence of thickness retention at the thinnest point of co-extrusion, change in hot mixing sequence, and violation of the surface / core layer viscosity ratio.
[0051] Table 1 Sample preparation variables Example 1 Weather-resistant surface layer + structural core layer co-extrusion Complete collaborative system The weather-resistant surface layer is coated with TiO2, CeO2, hydrotalcite, and HALS / UVA gradient enrichment; the target thickness of the thinnest surface layer at the edge is about 0.240 mm, and the actual measured thickness is about 0.232 ± 0.013 mm; the surface layer / core layer viscosity ratio is about 1.04. Comparative Example 1 Single-layer homogeneous extrusion Industry baseline formulation It adopts the conventional PVC-U guardrail formula, with TiO2, CPE, calcium-zinc stabilizer and ordinary UVA / HALS added evenly across the entire cross section, without setting a surface / core layer structure. Comparative Example 2 Weather-resistant surface layer + structural core layer co-extrusion Removal of CeO2 and hydrotalcite / LDH Based on Example 1, nano-cerium oxide and hydrotalcite / LDH were removed, while the remaining co-extruded structure, calcium-zinc stabilizer, TiO2 coating, HALS / UVA and CPE / ACR system remained the same. Comparative Example 3 Ordinary co-extrusion Eliminate the thinnest point thickness preservation of complex cross-sections The surface layer formulation, core layer formulation, and hot mixing process are the same as in Example 1, but conventional average thickness flow channels are used, and no compensation is provided for the edges, snap grooves, and rib roots. Comparative Example 4 Weather-resistant surface layer + structural core layer co-extrusion Cancel segmented hot mixing The overall formulation is the same as in Example 1, but PVC, stabilizer, titanium dioxide, CeO2, HALS, UVA, CPE, ACR, filler and lubricant are added and hot-mixed at the same time. Comparative Example 5 Weather-resistant surface layer + structural core layer co-extrusion Surface / core viscosity ratio exceeds the limit The materials, feeding sequence, hot mixing endpoint, cold mixing, curing, and die head structure are the same as in Example 1, except that the surface melt temperature is reduced from 184.0℃ to 171.5℃, so that the surface / core apparent viscosity ratio is increased to 1.61. II. Testing Methods The guardrail profile samples prepared in each group were placed at 23℃ and 50% relative humidity for 24 hours before performance testing. Test items and methods are shown in Table 2. The powdering grade was recorded as a median and range from 0 to 5. The mass loss from wiping powdering was determined using a non-woven fabric wiping method with fixed pressure, fixed area, and fixed number of wiping cycles, and the mass of powdered material per unit area was measured, expressed as mg / cm². Cracking of the snap-fit grooves was determined by counting the number of cracks in 50 snap-fit groove samples, expressed as crack count / 50.
[0052] Table 2 Test Items and Testing Basis Accelerated weather resistance QUV after 2000h: color difference ΔE on flat surfaces and edges, wiping chalking quality, and chalking grade. Fluorescent UV aging chamber, integrating sphere spectrophotometer Compliant with ASTM G154, ISO 4892-3, and GB / T 16422.3-2022; color difference is calculated according to ASTM D2244. Impact performance Impact strength and impact retention rate of notched simply supported beams before and after aging Pendulum impact testing machine, notch sample preparation machine ISO 179-1. Bending performance Flexural modulus Electronic universal testing machine, three-point bending fixture ISO 178. Heat distortion properties Vicat softening temperature Vicat softening temperature tester ISO 306. Melt Rheology Surface / core layer melt apparent viscosity ratio Rotational rheometer or dynamic mechanical rheometer The test was conducted at 185°C and a shear rate of 100 s⁻¹; refer to ASTM D4440. Cross-section thickness preservation Surface thickness, thinnest surface thickness at the edge, thinnest thickness / depth of aging effect Optical microscope, microtome, image analysis software Measurements were taken after slicing the profile section; the depth of aging effect was determined by the layer-by-layer ATR-FTIR carbonyl index. Distribution of elements and auxiliaries Surface / core Ti signal ratio, Ce signal, and HALS / UVA dwell rate SEM-EDS, micro-area XRF, ATR-FTIR, Py-GC / MS, or LC-MS Elemental gradients can be referenced in ASTM E1508; infrared quantification can be referenced in ASTM E168. Processing Hot mixing current fluctuation, die pressure fluctuation, screen residue, unit extrusion energy consumption Online current acquisition system, extrusion pressure sensor, energy consumption meter Record using internal process control methods. III. Test Results The processing parameters and cross-sectional structure test results of each group of samples are shown in Table 3A.
[0053] Table 3A: Processing procedure and cross-sectional structure test results Example 1 4.82±0.46 0.56±0.08 27.4±3.6 0.159±0.006 1.04±0.04 0.318±0.014 0.232±0.013 Comparative Example 1 8.74±0.81 0.88±0.13 52.9±6.4 0.143±0.005 not applicable not applicable not applicable Comparative Example 2 4.31±0.40 0.63±0.09 25.8±3.1 0.153±0.005 1.03±0.05 0.316±0.016 0.229±0.014 Comparative Example 3 4.67±0.49 0.72±0.10 29.1±3.9 0.156±0.006 1.05±0.04 0.317±0.018 0.091±0.012 Comparative Example 4 14.86±1.22 1.41±0.21 97.6±10.8 0.171±0.008 1.10±0.07 0.304±0.027 0.205±0.024 Comparative Example 5 5.06±0.55 2.18±0.29 43.7±5.9 0.184±0.010 1.61±0.08 0.339±0.031 0.121±0.019 The aging depth and weathering agent distribution test results for each group of samples are shown in Table 3B.
[0054] Table 3B Results of Aging Depth and Weathering Agent Distribution Tests Example 1 0.123±0.009 1.89±0.17 4.55±0.25 The layer content was 0.118 ± 0.014 wt%, and the core layer content was close to the limit of quantification. 87.6±3.1 Comparative Example 1 0.254±0.026 not applicable 1.02±0.07 Not detected 55.7±4.8 Comparative Example 2 0.174±0.015 1.32±0.15 4.48±0.28 Not detected 65.1±3.7 Comparative Example 3 0.126±0.011 0.72±0.11 4.59±0.31 Surface enrichment exists 86.1±3.0 Comparative Example 4 0.193±0.020 1.06±0.16 4.21±0.42 Surface enrichment but high dispersion 60.3±4.5 Comparative Example 5 0.129±0.012 0.94±0.17 4.50±0.34 Surface enrichment exists 85.8±3.2 The appearance and weather resistance properties of each group of samples after QUV aging for 2000h are shown in Table 4.
[0055] Table 4. Results of Appearance Weather Resistance Test Example 1 2.28±0.19 2.76±0.27 0.18±0.04 1 / 0-1 Comparative Example 1 6.42±0.53 6.71±0.60 0.86±0.11 4 / 3-5 Comparative Example 2 4.15±0.38 4.82±0.45 0.54±0.08 3 / 2-4 Comparative Example 3 2.83±0.25 8.21±0.77 0.93±0.13 (edge region) 4 / 3-5 (Edge Area) Comparative Example 4 5.18±0.46 5.77±0.52 0.69±0.10 3 / 2-4 Comparative Example 5 4.61±0.42 8.95±0.82 1.04±0.15 (edge region) 4 / 3-5 (Edge Area) The test results of mechanical properties, thermal properties and structural stability of each group of samples are shown in Table 5.
[0056] Table 5. Test results of mechanical properties, thermal properties and structural stability Example 1 18.1±0.8 13.5±0.7 74.6±4.2 2862±58 81.7±0.7 3.8±0.5 2 / 50 Comparative Example 1 16.5±0.9 7.4±0.6 44.8±4.6 2748±64 80.3±0.8 6.9±0.8 12 / 50 Comparative Example 2 17.6±0.7 10.3±0.8 58.5±4.8 2851±52 81.1±0.7 4.9±0.6 8 / 50 Comparative Example 3 18.0±0.8 9.5±0.9 52.8±5.0 2859±55 81.9±0.6 5.2±0.7 14 / 50 Comparative Example 4 17.0±1.0 9.1±0.8 53.5±5.2 2816±69 80.8±0.9 5.9±0.8 11 / 50 Comparative Example 5 17.2±0.9 7.9±0.7 45.9±4.9 2848±61 81.6±0.8 8.6±1.0 18 / 50 The process continuity indicators for each group of samples are shown in Table 6.
[0057] Table 6 Results of Process Continuity Test Example 1 1.65-1.88 7.8±0.6 38.6±2.4 21.8±1.9 Comparative Example 1 1.72-2.05 6.1±0.7 42.3±2.7 19.6±2.1 Comparative Example 2 1.66-1.92 7.1±0.8 39.8±2.5 21.2±2.0 Comparative Example 3 1.68-1.91 7.5±0.7 38.9±2.8 21.5±2.1 Comparative Example 4 1.45-1.72 3.2±0.5 35.1±3.6 16.2±2.4 Comparative Example 5 1.20-1.48 4.6±0.6 36.7±3.1 18.1±2.3 IV. Results Analysis As shown in Tables 3A-6, Example 1 outperforms the comparative examples in terms of maintaining thickness of exposed complex cross-sections, impact retention after aging, and crack resistance of the snap-fit groove. Compared with Comparative Example 1, the unit energy consumption of Example 1 is slightly higher, but its planar color difference after 2000h QUV is 2.28±0.19 and its edge color difference is 2.76±0.27, both lower than those of Comparative Example 1 (6.42±0.53 and 6.71±0.60). The impact retention rate of Example 1 is 74.6±4.2%, higher than that of Comparative Example 1 (44.8±4.6%). The number of snap-fit groove cracks is 2 / 50, lower than that of Comparative Example 1 (12 / 50).
[0058] In Comparative Example 2, after removing nano-cerium oxide and hydrotalcite / LDH, the depth of aging effect increased from 0.123±0.009 mm in Example 1 to 0.174±0.015 mm, and the impact retention rate decreased to 58.5±4.8%. These results indicate that nano-cerium oxide and hydrotalcite / LDH play a role in inhibiting the deepening of surface aging.
[0059] In Comparative Example 3, after eliminating the thinnest point of the complex cross-section, the color difference in the planar area was 2.83±0.25, while the color difference at the edges increased to 8.21±0.77, and the thinnest surface layer thickness at the edges was only 0.091±0.012 mm. This result indicates that controlling only the average surface layer thickness in the planar area cannot guarantee the weather resistance of exposed weak points such as edges and snap-fit grooves.
[0060] In Comparative Example 4, after single-stage hot mixing, the fluctuation of the hot mixing current and the residue on the screen increased significantly, the HALS / UVA retention rate decreased to 60.3±4.5%, and the appearance, weather resistance, and impact retention rate after 2000 hours of QUV treatment were inferior to those of Example 1. These results indicate that the staged hot mixing sequence affects the retention of the light stabilizer and the dispersion of the filler.
[0061] In Comparative Example 5, after lowering the surface melt temperature to 171.5℃, the surface / core viscosity ratio increased to 1.61, the thinnest surface layer thickness at the edges decreased to 0.121±0.019 mm, the edge color difference increased to 8.95±0.82, and the warpage after 80℃ heat exposure increased to 8.6±1.0 mm·m^-1. These results indicate that a surface / core viscosity ratio deviating from the set range reduces the surface coating stability of exposed areas with complex cross-sections.
[0062] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A modified material specifically for outdoor anti-aging PVC guardrails, characterized in that, It comprises a co-extruded weather-resistant surface layer and a structural core layer; the weather-resistant surface layer at least covers the exposed plane, exposed edges, chamfers, outer lip of the buckle groove, and outer area of the rib root of the PVC guardrail profile, accounting for 5.0%-24.0% of the total mass of the profile, the thinnest weather-resistant surface layer thickness in the exposed area is 0.12-0.60 mm, and the ratio of the thinnest weather-resistant surface layer thickness to the surface aging influence depth determined by the layer-by-layer carbonyl index method is 1.2-4.0; based on 100 parts of PVC resin in the weather-resistant surface layer, the weather-resistant surface layer includes 4.5-12.0 parts of rutile titanium dioxide coated on the surface, 0.05-0.80 parts of nano cerium oxide, 0.6-4.0 parts of layered double hydroxide or hydrotalcite, a lead-free calcium-zinc composite stabilizing system, and a light stabilizing system composed of high molecular weight hindered amine light stabilizers and benzotriazole or triazine UV absorbers.
2. The modified PVC fence material according to claim 1, characterized in that, The surface aging influence depth is the depth determined by removing material layer by layer from the outer surface to the inside of the profile sample after accelerated aging with fluorescent ultraviolet light and measuring the carbonyl index until the increment of the carbonyl index relative to the reference value of the unaged core layer is less than 10% and two consecutive layers meet this condition. The ratio of the thickness of the thinnest weather-resistant surface layer to the surface aging influence depth is 1.6-2.
8.
3. The modified PVC fence material according to claim 1, characterized in that, The surface-coated rutile titanium dioxide has a particle size D50 of 0.18-0.42 μm and a surface coating of one or more inorganic coatings selected from silicon dioxide, alumina, and zirconium oxide, with a coating amount of 1.5%-8.0% of the titanium dioxide mass; the nano-cerium oxide has a particle size D50 of 20-120 nm; and the Mg / Al molar ratio of the layered double hydroxide or hydrotalcite is 1.8-4.
0.
4. The modified PVC fence material according to claim 1, characterized in that, The lead-free calcium-zinc composite stabilizing system comprises 2.5-6.5 parts of calcium-zinc composite stabilizer, 0.05-0.60 parts of β-diketone auxiliary stabilizer, 0.05-0.50 parts of phosphite antioxidant, and 0.03-0.35 parts of hindered phenol antioxidant; wherein the Ca / Zn molar ratio of the calcium-zinc composite stabilizer is 2.0-7.0; the light stabilizing system comprises 0.20-1.20 parts of high molecular weight hindered amine light stabilizer with a number average molecular weight of 900-6000 g / mol, and 0.20-1.20 parts of benzotriazole or triazine UV absorber.
5. The modified PVC fence material according to claim 1, characterized in that, The weather-resistant surface layer also includes an impact-modifying system, fillers, and a lubrication system; the impact-modifying system includes 2.0-9.0 parts of CPE, 2.0-8.0 parts of core-shell ACR impact modifier, and 0.6-2.2 parts of processing aid ACR; the fillers include 4-25 parts of surface-modified calcium carbonate and 2-14 parts of flake mica powder or talc powder; the lubrication system is used in an amount of 0.4-1.5 parts; the structural core layer is based on 100 parts of PVC resin. It includes 0.3-4.0 parts of rutile titanium dioxide, 2.5-5.5 parts of calcium-zinc composite stabilizer, 0.3-2.5 parts of hydrotalcite or layered double hydroxide, 3.0-8.0 parts of CPE, 1.0-5.0 parts of core-shell ACR impact modifier, 0.5-1.8 parts of processing aid ACR, 8-25 parts of surface-modified calcium carbonate, 2-14 parts of flake mica powder or talc powder, and 0.5-1.5 parts of lubrication system.
6. A method for preparing a modified material specifically for outdoor anti-aging PVC guardrails, characterized in that, include: Prepare surface dry mix and core dry mix separately; The surface dry mix undergoes three stages of hot mixing. In the first stage, PVC resin is hot-mixed with calcium-zinc composite stabilizer, hydrotalcite, β-diketone auxiliary stabilizer, phosphite antioxidant, hindered phenol antioxidant, and part of the internal lubricant. In the second stage, rutile titanium dioxide with surface coating, nano-cerium oxide pre-dispersed with surface-modified calcium carbonate, and fillers are added. In the third stage, high molecular weight hindered amine light stabilizer, benzotriazole or triazine UV absorber, CPE, core-shell ACR impact modifier, processing aid ACR, and the remaining lubricant are added. At 185°C and a shear rate of 100 s^-1, when the ratio of the apparent viscosity of the surface melt to the apparent viscosity of the core melt is 0.70-1.45, the mixture is co-extruded through the core main channel and the surface distribution channel. The surface distribution channel covers the exposed plane, exposed edges, the outer lip of the snap-fit groove, and the outer area of the rib root, and has at least an edge compensation branch. The mixture is then vacuum-formed, stepped cooled, and cut into shape.
7. The preparation method according to claim 6, characterized in that, Before production, PVC resin, titanium dioxide, surface-modified calcium carbonate, flake mica powder, hydrotalcite and nano-cerium oxide are placed in a sealed transfer silo for 4-12 hours to balance. The hot mixing adopts a vertical high-speed hot mixer with three-layer angled blades. The hot mixer filling rate is controlled at 60%-80%, and the unit loading power during the hot mixing stage is controlled at 0.18-0.32kW / kg.
8. The preparation method according to claim 6, characterized in that, The first stage of hot mixing raises the material temperature to 70-80℃; the second stage of hot mixing raises the material temperature to 90-100℃; the third stage of hot mixing raises the material temperature to 113-116.5℃. The surface material hot mixing endpoint also meets the following requirements: the main motor current fluctuation is no greater than ±4.5% within 60 seconds; no wax spots appear after the sampled powder is lightly pressed with a glass plate; and the mass of agglomerates on the 2.0mm sieve is less than 0.15% when sieved 30 minutes after discharge.
9. The preparation method according to claim 6, characterized in that, The surface distribution channel is equipped with replaceable flow-limiting gaskets in the planar area, edge area, and snap-fit groove area. The opening height of the flow-limiting gasket in the planar area is 0.16-0.28 mm, the opening height of the edge compensation branch is 0.18-0.32 mm, and the opening height of the snap-fit groove outer lip compensation branch is 0.20-0.34 mm. The measured temperature of the core melt during co-extrusion is 170-185℃, and the measured temperature of the surface melt is 176-190℃.
10. The preparation method according to claim 6, characterized in that, When the preform enters the first stage of the vacuum forming table, the negative pressure is -0.040 to -0.085 MPa. The cooling water temperatures of the first, second, third, and fourth stages are 30-40℃, 24-32℃, 18-24℃, and 12-18℃, respectively. Before entering the first stage of vacuum forming after the preform exits the mold, the wet layer thickness of the exposed surface is 0.380-0.410 mm, and the wet layer thickness of the edges and snap-fit grooves is 0.285-0.320 mm. After vacuum calibration, traction stretching, and cooling shrinkage, a dry surface layer of 0.300-0.340 mm is formed on the surface, and the thinnest surface layer of the edges and snap-fit grooves is 0.215-0.265 mm.